Efusi Pleura Masif Hemoragik Akibat Keganasan: Laporan Kasus - Lulu Setyawati Purwaningsih; Krisbiyanto (Jurnal Ilmiah Kedokteran dan Kesehatan, 2026)
Pleural effusion is an accumulation of excess fluid in the pleural cavity, and can be classified as transudate and exudate. Transudate effusion occurs because of other diseases not primary to the lungs such as liver cirrhosis. Exudate efusion happens when there are inflammatory processes in pleura such as terror, tuberculosis (TB), and parapneumonia. Hemorrhagic pleural effusion occurs due to inflammatory processes. A 71-year-old woman complained of a sickness, a pain in the chest a day before she was admitted to the hospital, a relieved pain while lying down, and an unproductive cough and chest pain on her left side. An abnormal physical examination resulted in a faint sound and a decreased basal vesicular voice on the left chest. The thorax photo resulted in a massive effusion covering the left hemithorax. CT scan showed the pulmonary mass on the left. The cytological results indicate the presence of an inflammatory process. After performing Water Sealed Drainage (WSD), a concentrated red fluid of 2250 cc is produced. The patient was diagnosed with comparative pleural effusion due to violence, tuberculosis, and pulmonary Ca. The patient's diagnosis is a hemorrhagic massive pleural effusion with the cause of violence. The diagnosis of TB and pneumonia is eliminated because there is no TB trias and the pleural fluid is not colored green, yellow and purulent.